Similaridade das dietas de bugios (Alouatta spp.): proposta de método de análise e consistência intergrupo - Lisboa, Flávia Martins (2019)
Metabolic differences resulting from body size, sex and age are responsible for distinct energy and nutritional demands and may result, among other interindividual differences, in diets with distinct characteristics. Therefore, comparative studies of the feeding behavior of individuals in a social group are important to understand the strategies used to fulfill their requirements while sharing the same resources. In this study, I develop a method to evaluate the diet similarity of sex-age classes of 12 free-ranging howler monkey groups inhabiting forest fragments in the state of Rio Grande do Sul (eight groups of Alouatta guariba clamitans and four of A. caraya). I analyze the diet at three levels: (1º) food item (e.g. leaf, fruit, flower etc.), (2º) item and species (e.g. leaf of species X, fruit of species Y, flower of species Z etc.) and (3º) item, maturity and species (e.g. young leaf of species X, green fruit of species Y etc.). I also evaluate whether variations in qualitative and quantitative resource availability resulting from environmental seasonality and habitat size (forest fragment size) influence dietary similarities. The similarities between sex-age classes were consistent in the three levels of analysis, which suggests that information at the level of food item is sufficient to identify the general pattern of similarity of the diets of the sex-age classes. The adult female class exploited the diet most similar to the other classes, while the adult male and subadult male classes exploited the most divergent diets. The small difference in the diets of adult females and males was caused mostly by a higher ingestion of leaves by males and of fruits by females. The importance of bark in the distinction of the diets of immatures is probably related to the role of calcium during growth. Environmental seasonality and fragment size did not influence diet similarity. In summary, the members of a howler monkey group exploit resources in similar way, which may be a consequence of their social cohesion, the exploitation of a standard diet that meets the nutritional and energy demands of all independent individuals and/or their ability to metabolize the same food differently due to distinct gut microbiota.